การวิเคราะห์สถานการณ์การดูแลผู้ที่ได้รับการล้างไตผ่านทางช่องท้องอย่างต่อเนื่อง อำเภอดอกคำใต้ จังหวัดพะเยา - อัจฉรา พรหมเสน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Continuous ambulatory peritoneal dialysis (CAPD) is treatment for people who suffer from end stage renal failure. There are many problems associated with ambulatory peritoneal dialysis, including infection and wrong practices. This study aimed to make situational analysis of the care of persons with CAPD in Dok Khamtai Sub-district, Dok Khamtai District, Phayao Province. System theory (Von Bertalunffiy, 1968) was used in the study, consisting of a procedure of input, process and output. The study was conducted with, 1) persons with continuous ambulatory peritoneal dialysis, 2) 10 caregivers caring for persons with continuous ambulatory peritoneal dialysis, and 3) 3 health personnel who work in the division of continuous ambulatory peritoneal dialysis. Instruments used in the study were guidelines for focus group discussion and individual interview scripts. Accuracy of content validity and appropriateness of language were approved by 3 experts. Data were analyzed by using descriptive statistics and content organization. Results from the study showed that: 1. Input factors including rooms built for the ambulatory peritoneal dialysis were convenient and suitable. However, there were not enough cleaning tools to respond to the patient’s needs. Attendants received documents and guide books with complete content on CAPD, and they had books recording fluid intake and outtake from the patient’s bodies. Attendants had knowledge of wound care and catheter treatment, but they did not clean wounds or catheter joints well enough. Moreover, they forgot the procedures of peritoneal ambulatory dialysis, and were not give important on eating habit. Health personnel at Phayao Hospital, inclusive of 1 specialist and 2 CAPD nurses, were responsible for taking care of 127 CAPD patients. Therefore, CAPD staffs responsibilities were beyond their working capacity. In addition a health team normally visits the patients at home once a year, and personnel, attendants and patients should receive knowledge about peritoneal ambulatory dialysis once a year also. 2. Process factors showed that patients and attendants had knowledge about how to do ambulatory peritoneal dialysis and wound care around the catheter exit site. However, they had incorrect knowledge and practices, such as using non-sterile cotton swabs, not washing their hands, performing dialysis too quickly, and with a lack of equipment for wound care and dialysis. Patients demonstrated symptoms of stomachache, fever, turbid peritoneal dialysis solution, pus, swelling, and red wounds. 3. In terms of output, from the 45 persons with end stage renal failure it was found that 22% (or 10 persons) had complications and infections. They experienced stomachache, fever, turbid peritoneal dialysis solution, pus, swollen, and red wounds. Therefore, they had to see doctors and stay at the hospital. Results from this study can be used to develop effective treatment systems for patients who have continuous ambulatory peritoneal dialysis in Dok Khamtai Sub-district, Dok Khamtai District, Phayao Province.